Shade Determination in Anterior Teeth with Spectrophotometer and Digital Camera in The Making of Fixed Partial Dentures : (Systematic Literature Review) - Saffa A. Natascha; Sri Wahyuningsih Rais; Danica Anastasia (Dentistry Study Program, Faculty of Medicine Universitas Sriwijaya, 2022)
Introduction: Fixed partial denture is a prosthesis that is permanently attached to one or more damaged teeth, or to replace missing teeth. Shade determination was one of the first step in restoration procedures or making dentures. Restoration could be a failure due to the selection of an inappropriate tooth shade, especially in the replacement of anterior teeth that have high requirements to support appearance and aesthetics. The use of a spectrophotometer and digital camera could help dentists in choosing tooth shades. Purpose: The purpose of this study was to determine and analyze differences in the color accuracy of anterior teeth using a spectrophotometer and digital camera in the manufacture of fixed partial denture. Method: This study used a systematic literature review with fifteen journals.The type of research was a survey and cross-sectional so that the bias analysis will use the Critical Appraisal Skills Program (CASP) and the data extraction in this study also uses a form according to CASP. The data obtained will be synthesized qualitatively. Result: This study showed that seven out of fifteen journals reported that the use of a spectrophotometer in the tooth shade determination provided an accurate result in the selection of anterior tooth shade, while eight other journals stated that the use of a digital camera could be an alternative in choosing tooth shade because digital cameras are easy to get and could combine color features to produce accurate colors. Conclusion: Spectrophotometers and digital cameras could provide good results in terms of shade accuracy and precision.